2017
DOI: 10.5851/kosfa.2017.37.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Antioxidants and Quality Characteristics from Velvet Antlers of Formosan Sambar Deer

Abstract: The quality characteristics of velvet antlers obtained from Formosan sambar deer (Cervus unicolor Swinhoi) (SDVA), harvested from 63 to 81 d during the velvet antler growth period, were evaluated by investigating the relationships between antioxidant levels; including content, activity, and content/activity ratios, and physical properties; including shear force values, color, and Ca content. The hardness of samples from base velvet antler sections increased, and that the color of these samples tended to become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The appearance and composition differences between slides of SVA and RVA might be partly due to the harvested method and growing period of the velvet antlers. Cheng et al [ 18 ] indicated that the hardness of VA sections increased, and that the color of these samples tended to become reddish-yellow due to the Ca content in the base section without ossifying. Jeon et al [ 19 ] also indicated that growth periods of antlers affected the chemical compositions of VA.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance and composition differences between slides of SVA and RVA might be partly due to the harvested method and growing period of the velvet antlers. Cheng et al [ 18 ] indicated that the hardness of VA sections increased, and that the color of these samples tended to become reddish-yellow due to the Ca content in the base section without ossifying. Jeon et al [ 19 ] also indicated that growth periods of antlers affected the chemical compositions of VA.…”
Section: Discussionmentioning
confidence: 99%
“…Among TCM treatments, deer velvet antler (VA) has been exploited for medicinal purpose for more than 2,000 years and possesses various pharmacological benefits, such as improvement of the physical strength, sexual function, and immunity [ 2 , 7 ]. VA has a cartilaginous composition and is usually found in members of Cervidae family, which includes elk, deer, moose, and caribou [ 7 ]. The global supply of antlers usually comes from the red deer ( Cervus elaphus ), sika deer ( C. nippon ), elk ( C. canadensis ), or wapiti ( Elaphurus davidianus ).…”
Section: Introductionmentioning
confidence: 99%
“…Su-Hyeon Kim 1 , Kashif Ameer 2,3 , Jun-Hyun Oh 4 , Mi-Kyung Park 1,5 * several pharmacological benefits for immune, cardiovascular, nervous and reproductive systems and are used frequently to develop functional foods, nutraceutical supplements and other medicinal products (Jang et al, 2020;. Bioactive compounds from animal sources include essential oils, vitamins, minerals, dietary fiber, peptides, protaglandinds, glycoaminoglycans, proteins and fatty acids (Cheng et al, 2017). All these bioactive compounds are widely employed in pharmaceutical sector to prepare medicines and supplements to mitigate lifestyle related disorders (Sui et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%